ANALISIS HUBUNGAN ANTARA MOTIVASI INTRINSIK DAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Maulana Rizqi; Nursyipa; Husnul Khotimah; Adelia Sofirin; Maimunah; Ahmad Suriansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to provide teachers with a deeper understanding of the factors thatinfluence the learning achievement of elementary school students, enabling them todesign more effective instructional strategies aligned with students’ needs. Thisresearch employs a literature review method by examining various sources discussing the roles of internal and external factors in determining students’academic performance. The internal factors analyzed include physical condition,psychological aspects, and cognitive abilities, while the external factors consist offamily environment, school environment, and community environment. The findingsindicate that learning achievement can be improved when teachers are able toidentify the causes of students’ learning difficulties through these two categories offactors and adjust their teaching approaches accordingly. Teachers are able tocreate more interactive and supportive learning experiences when they understandhow personal conditions and environmental influences shape students’ academicoutcomes. These results highlight the essential role of teachers in optimizinglearning achievement through the management of influential factors surrounding thelearning process.